Cell penetrating, mitochondria targeting multiply charged DABCO-cyanine dyes. (November 2018) - Kurutos, Atanas; Orehovec, Iva; Saftić, Dijana; Horvat, Lucija; Crnolatac, Ivo; Piantanida, Ivo; Deligeorgiev, Todor
Abstract: We have prepared new series of lipophilic cyanine dyes equipped with several cationic quaternary ammonium moieties. This was achieved by introducing DABCO within the structures. Furthermore, to investigate the influence of the additional cationic charges on the cellular uptake, DABCO was quaternized with methyl group or alkyl piperidine cation. Spectroscopic and isothermal titration calorimetry studies as well as MTT assay and subcellular localization using confocal laser scanning microscopy revealed that some of the presented dyes combine low anti-proliferative effect with efficient cellular uptake, high affinity towards ds-DNA/RNA and remarkable fluorescent marking of mitochondria. Graphical abstract: Image 1 Highlights: New DABCO-cyanine dyes dyes bind with high affinity to ds-DNA/RNA. Relatively low anti-proliferation effect. Fluorescence emission increase upon binding ds-DNA/RNA. Fluorescence emission in the live cells. A and B1 co-localize with the MitoTracker ® dye.